Express experimental evalution of mutagenic activity of complex phoshorus-containing organic mixtures = Експрес-експериментальна оцінка мутагенної активності складних фосфоровмісних органічних сумішей = Экспресс-экспериментальная оценка мутагенной активности сложных фосфоросодержащих органических смесей - Bagmut, I. Yu.; Zharova, N. V.; Popova, T. M.; Zhukov, V. I.; Stetsenko, S. O. (Journal of Education, Health and Sport, 2016)
Bagmut I. Yu., Zharova N. V., Popova T. M., Zhukov V. I., Stetsenko S. O. Express experimental evalution of mutagenic activity of complex phoshorus-containing organic mixtures = Експрес-експериментальна оцінка мутагенної активності складних фосфоровмісних органічних сумішей = Экспресс-экспериментальная оценка мутагенной активности сложных фосфоросодержащих органических смесей Journal of Education, Health and Sport. 2016;6(10):443-454. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164190 http://ojs.ukw.edu.pl/index.php/johs/article/view/3971 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. UDK 579.695 EXPRESS EXPERIMENTAL EVALUATION OF MUTAGENIC ACTIVITY OF COMPLEX PHOSPHORUS-CONTAINING ORGANIC MIXTURES I. Yu. Bagmut, N. V. Zharova, T. M. Popova, V. I. Zhukov, *S. O. Stetsenko Kharkiv Medical Academy of Postgraduate Education; *Kharkiv National Medical University Summary Researching the mutagenic activity of organic phosphorus-containing mixtures of Esherichia Coli bacteria strain trp A 223 and the continuous cells culture of murine myeloma X63 also detected the presence of weak mutagenic properties in this group of xenobiotics. The concentrations of all compounds 400 and 1000 mg/l have bacteriostatic effect, and their lower concentrations in the range from 10 to 80 mg/l stimulate the mutagenic activity. Phosphorus-containing organic compounds can inhibit the synthesis of proteins, RNA and DNA in cell culture Vero depending on the concentration. Key words: xenobiotics, carcinogenesis, mutagenesis, atherogenesis, suppression of immune deficiency, reproductive function, Esherichia Coli, cells culture of murine myeloma X63. ЕКСПРЕС-ЕКСПЕРИМЕНТАЛЬНА ОЦІНКА МУТАГЕННОЇ АКТИВНОСТІ СКЛАДНИХ ФОСФОРОВМІСНИХ ОРГАНІЧНИХ СУМІШЕЙ І. Ю. Багмут, Н. В. Жарова, Т. М. Попова, В. І. Жуков, * С. О. Стеценко Харківська медична академія післядипломної освіти; *Харківський національний медичний університет, м. Харків Резюме Дослідження мутагенної активності фосфорвмісних органічних сумішей на бактеріях Esherichia Coli штам trp A 223 і перевиваємій культурі клітин мишачої мієломи Х63, виявили наявність слабких мутагенних властивостей досліджуваних ксенобіотиків. Всі сполуки в концентраціях 400 і 1000 мг/л володіють бактеріостатичним ефектом, а в більш низьких концентраціях в діапазоні від 10 до 80 мг/л вони стимулюють мутагенну активність. В залежності від концентрації, фосфорвмісні органічні сполуки здатні пригнічувати синтез білків, РНК і ДНК в культурі клітин Vero. Ключові слова: ксенобіотики, канцерогенез, мутагенез, атерогенез, пригнічення імунологічної недостатності, репродуктивна функція, бактерії Esherichia Coli, клітини мишачої мієломи Х63. ЭКСПРЕСС-ЭКСПЕРИМЕНТАЛЬНАЯ ОЦЕНКА МУТАГЕННОЙ АКТИВНОСТИ СЛОЖНЫХ ФОСФОРОСОДЕРЖАЩИХ ОРГАНІЧЕСКИХ СМЕСЕЙ И. Ю. Багмут, Н. В. Жарова, Т. М. Попова, В. И. Жуков, *С. О. Стеценко Харковская медицинская академия последипломного образования; *Харковский национальный медицинский университет, г. Харьков Резюме . Исследования мутагенной активности фосфосодержащих органических смесей на бактериях Esherichia Coli штамм trp A 223 и перевиваемой культуре клеток мышиной миеломы Х63 выявили наличие слабых мутагенных качеств исследованных ксенобиотиков. Все соединения в концентрациях 400 і 1000 мг/л обладают бактериостатическим эффектом, а в больших концентрациях в диапазоне от 10 до 80 мг/л они стимулируют мутагенную активность. В зависимости от концентрации, форсфорсодержащие органические соединения способны угнетать синтез белков, РНК и ДНК в культуре клеток Vero. Ключевые слова: ксенобиотики, канцерогенез, мутагенез, атерогенез, угнетение иммунологической недостаточности, репродуктивная функция, бактерии Esherichia Coli, клетки мышиной миеломы Х63.